Building Strong Primary Health Care to Tackle the Growing Burden of Non-Communicable Diseases in Nepal - Bishal Gyawali; Pratik Khanal; Shiva Raj Mishra; Edwin van Teijlingen; Dan Wolf Meyrowitsch (Taylor & Francis Group, 2020)
Nepal is currently facing a double burden of non-communicable diseases (NCDs) and communicable diseases, with rising trends of NCDs. This situation will add great pressure to already fragile health systems and pose a major challenge to the country's development unless urgent action is taken. While the primary health care approach offers a common platform to effectively address NCDs through preventive and curative interventions, yet its potential is not fully tapped in Nepal. In line with the Alma Ata and Astana Declarations, we propose an integrated approach for Nepal, and other low-and middle-income countries, including six key reforms to enhance the primary care response to the increasing burdens of NCDs.